COLLABORATIVE GOVERNANCE DALAM REVITALISASI KAWASAN KUMUH DI KOTA PEKANBARU TAHUN 2023 - Siregar, A Timbul R; Pane, Rico Purnawandi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research is motivated by the rapid population growth in Pekanbaru City which raises the problem of slum areas. The Pekanbaru City Government is trying to overcome this problem through a slum revitalization program with the collaboration of government, community, and Tentara Manunggal Masuk Desa, but without involving the private sector as the ideal Collaborative Governance concept. This research aims to find out how government collaboration in slum revitalization in Pekanbaru city in 2023. This research uses a qualitative approach with descriptive methods. The types of data are primary data and secondary data, primary data obtained directly from informants. While secondary data is supporting data or strengthening primary data. Data collection techniques are carried out by means of interviews and documentation. This research uses the theory of collaborative governance from the theory of Hansell and gash (2008). The results of research and discussion regarding Collaborative Governance in Revitalizing Slum Areas in Pekanbaru City in 2023. Researchers can conclude that the Collaborative Governance process in revitalizing slum areas in Pekanbaru City has not been carried out optimally and has not shown strong collaboration between each stakeholder, this can be seen from the collaboration processes between the Public Housing and Settlement Areas Office, Community Self-Help Institutions and the 0301 Military District Command. Keyword: Revitalization, Collaboration, Settlements